The Effect of Job Training, Motivation, and Work Ethic to the Workforce Performance - Rike Kusuma Wardhani (Institute of Computer Science (IOCS), 2022)
Problems focussed of the research are job training, work motivation, and work ethic of employees at UD. Semanggi Mas Sejahtera. The study took the sample with predetermined criteria of 51 respondents who had carried out training activities, with the sampling technique using purposive sampling. The technique used to analyze the data is the validity and reliability test, multiple linear regression test, classical assumption test, and hypothesis test through t-test and F-test. The results indicated that the regression equation Y = 11.205 + 0.173 X1 + 0.462 X2 + 0.631 X3. Partially job training has a significant effect on workforce performance at UD. Semanggi Mas Sejahtera. Partially work motivation has a significant effect on workforce performance at UD. Semanggi Mas Sejahtera. Partially work ethic has a essential effect on workforce performance at UD. Semanggi Mas Sejahtera. Simultaneously job training, motivation, and work ethic have a significant effect on workforce performance at UD. Semanggi Mas Sejahtera. It is hoped that the company will further increase the intensity of job training in the company, and pay attention to policies regarding work motivation and work ethic so that workforce performance can be achieved.